Indicadores del desarrollo psicomotor fino presentes y ausentes en los niños/as de 5 años de I.E del nivel inicial del distrito de Rioja - Cubas Cabanillas, Edelmira (2016)
The present investigation consited in identifying and examining the point of fine psychomotor development that have or don't have five years old girls and boys, so that we take as a reference the educational institutions of initial levels which are located in Riojas district. lnvestigation emerged due to our interest for analazing the status of the fine psychomotor derelopment of girls and boys, so general objective consisted in knowing the incidence of the indicator that explain the fine psychomotor development that takes into account the background and actual theories that these indicators present in high measure which constituted the hypothesis of our investigation. In the operativa part, we wurred with a population proof conformad by 59 boys and 55 girl who were evaluated by a collition roll that takes into account indicators for visual motor, facial phonetic and gestural motrivity. In that way, investigation was conducted under a simple descriptiva design, formulating the statical hypothesu with a 95% trustworth, level to the countrastation of the hypothesu and according to datas nature, we used the normal proof for the proportional population arriving as a conclusion that there are high level indicator of fine psychomotor developments presents than absents in five years old boys and girls of educativa institution of initial level of Riojas district , in fact that 86% of boys and girls present in high level the indicators of fine psychomotor development in visual handed coordination, 74% in facial motrocity , 85% in phonetic motrocity and 80% in gesture motrocity